Identification of a novel class B scavenger receptor homologue in Portunus trituberculatus: Molecular cloning and microbial ligand binding. (November 2016) - Yang, Ning; Zhang, Dan-Feng; Tao, Zhen; Li, Meng; Zhou, Su-Ming; Wang, Guo-Liang
Abstract: Class B scavenger receptors (SRBs), which are present in mammals and insects, have been implicated in a wide range of functions. Herein, a novel SRB homologue, Pt SRB, was cloned from the swimming crab, Portunus trituberculatus . Pt SRB has 538 amino acid residues, and it consists of two transmembrane regions, a large extracellular loop, and two intracellular tails. A phylogenetic analysis showed that Pt SRB distinctly clustered with Marsupenaeus japonicas SRB-1 and most Drosophila SRB homologues, including Croquemort, Peste, NinaD, and Santa Maria, but was separate from the Drosophila sensory neuron membrane protein, Mj SRB-2, and all vertebrate SRBs. Real-time quantitative PCR analyses showed that the Pt SRB gene was constitutively expressed in all tissues tested. When Pt SRB was overexpressed in human embryonic kidney 293T cells, it was distributed in the membrane and cytoplasm. Moreover, in vitro assays showed that r Pt SRB bound microbial lipopolysaccharide with low affinity, and lipoteichoic acid and peptidoglycan with high affinity. Pt SRB transcripts were down-regulated after challenge with Vibrio alginolyticus or white spot syndrome virus, but not after a Candida lusitaniae challenge. This study provides valuable data for understanding the role of SRBs in the host defense against microbial pathogens, which will facilitate future studies of host–pathogen interactions in crabs. Highlights: A novel class B scavenger receptor homologue was identified from Portunus trituberculatus. Pt SRB transcripts were ubiquitously expressed in all the examined tissues. Pt SRB transcripts were down-regulated in hemocytes to V. alginolyticus or WSSV challenge. Pt SRB was distributed in the membrane and cytoplasm when overexpressed in HEK293T cells. r Pt SRB bound microbial LPS with low affinity, and LTA and PGN with high affinity in vitro.